Adaptive Energy Management Algorithms in Smart Buildings A Data Driven Assessment of Energy Sustainability and Operational Efficiency (Scientific Journal of Research Studies in Future Mechanical Engineering, 2024)
The increasing integration of intelligent systems in the built environment has positioned smart buildings as a critical component of global energy sustainability strategies. Despite significant advancements in building automation and energy-efficient technologies, operational inefficiencies persist due to static control strategies and limited adaptability to dynamic occupancy, climatic conditions, and user behavior. This study presents a comprehensive data-driven assessment of adaptive energy management algorithms in smart buildings, focusing on their contribution to energy sustainability and operational efficiency. The research adopts a multi-layered methodological framework combining real operational energy consumption data, building performance indicators, and advanced algorithmic control strategies. Adaptive energy management algorithms, including machine learning-based predictive models and reinforcement learning control schemes, are evaluated in terms of their ability to optimize heating, ventilation, air conditioning, and electrical load distribution. The assessment framework integrates temporal energy demand analysis, occupancy-driven consumption modeling, and sensitivity-based performance evaluation to capture the complex interactions between building systems and user behavior. A comparative analysis is conducted between conventional rule-based energy management approaches and adaptive algorithmic strategies using empirical datasets derived from monitored smart building operations. Key performance indicators include energy use intensity, peak demand reduction, system responsiveness, and operational stability. The findings demonstrate that adaptive energy management algorithms significantly enhance energy sustainability by reducing overall energy consumption, improving load balancing, and increasing system resilience under variable operational conditions. Moreover, the results indicate measurable improvements in operational efficiency through reduced control lag, enhanced predictive accuracy, and optimized system coordination. This study contributes to the architectural and energy engineering literature by providing a structured, data-driven evaluation of adaptive energy management in smart buildings, bridging the gap between theoretical algorithm development and real-world building performance. The proposed assessment framework offers practical implications for architects, engineers, and policymakers aiming to integrate intelligent energy control strategies into sustainable building design and operation. The outcomes support the transition toward performance-oriented, adaptive architectural systems capable of responding effectively to evolving energy and environmental challenges.